Roadside sculptures in Alor Gajah, Melaka: a case study / Azahar Harun ... [et al.] - Harun, Azahar; Abu Hassan, Sharmiza; Zakaria, Rosli; Abdullah, Ramlan; Legino, Rafeah; Adanam, Akmal; Supar, Shaharudin; Bebit, Mohd Ali Azraei; Mohamad Khalil, Musaddiq (Universiti Teknologi MARA, Perak, 2021)
Many municipal councils in Melaka have been installing roadside sculptures for demarcating territory, symbolizing local community, culture, history as well as promoting local tourism. In spite of that, this particular street facility is rarely discussed in the context of public art. Hence, this case looks at the roadside sculptures installed by Alor Gajah Municipal Council (MPAG) in terms of design and meaning. There were fourteen (14 nos) units of Roadside Sculptures (RS) along Alor Gajah- Melaka- Jasin (AMJ) highway that stretches 19.2 km from the entry point at Simpang Ampat toll plaza until Cheng had been sampled. In addition, observations and interviews with the town planning department representatives were also conducted. From the analysis, it is learned that the 14 RS units serve not only as a typical demarcation tool but also represents the state government’s initiative to introduce Melaka as a green technology city state. This manifestation can be observed by the design elements of flora, globe, leaf, hand gesture as well as the use of industrial materials such as solar panels and stainless steel. Nevertheless, their appearance felt static and senseless due to the fact that the designs were replicated. It is hoped that the findings of the study could aid municipal councils in Malaysia in making decisions on future urban ornamentation projects.